The Role of Toxoplasmosis in Ophthalmic Disorders - J Saki; MJ GHaravi; SH Khademvatan (Tehran University of Medical Sciences, 2007)
Introdution: Toxoplasosis is a parasitic infection that created by protozoan named Toxoplasma gondii. A definitive host is cat and intermediate hosts are mammalian and birds (tissue cyst in organs). Human be infected via ingestion oocyst and row or undercooked contaminated meat. The causative agent transforms to tissue cyst in the divers organs especially in eye and bring about O.T .The majorities of cases are asymptomatic but the protozoan can locate in the eye and create acute corioritinite .The most prevalent causative agent of corioritinite is toxoplasmosis and it is estimated that 35% of corioritinite cases in children and adult, attributed to toxoplasma gongii Methods: Many articles about pathologic effects, prevalence, life cycle of toxoplasma gongii affected groups and ontrol of the infection have been studied. Resultss: Ocular toxoplasmosis in the human manifests most commonly following congenital infection. Experimentally it is showed that 5.3% of the mice offspring going on to develop bilateral or unilateral cataracts. Lymphocytes and macrophages were seen to enter the eye and the presence of degraded photoreceptor segments within macrophage phagolysosomes was shown. Retinal pigment epithelial cells (RPE), were also found to migrate, enter the eye and participate in phagocytosis. Conclusion: Because to high prevalence of toxoplasmosis (70% in some regions) it is deserved that toxoplasmosis be considered as a main causative agnate of corioritinite and ophtalmogists insert toxoplasma gongii as a causative agent in the clinical table.